Aluminum alloy materials, precision instrument parts, and methods for manufacturing aluminum alloy materials
Patent Information
- Application Number
- JP2025057547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0011】 前記アルミニウム合金材における、最長径7μm以上10μm未満の第二相粒子が100個/mm2以上である。これにより、前記第二相粒子とAlマトリクス中の転位との相互作用によって前記アルミニウム合金材の外部から加わる振動を効率よく減衰させることができる。その結果、従来のアルミニウム合金材よりも制振性を高めることができる。
Smart Images

Figure 2026165257000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to aluminum alloy materials, precision instrument parts, and methods for manufacturing aluminum alloy materials. [Background technology]
[0002] In various fields such as industrial products, buildings, and structures, vibrations generated during equipment use or from external sources can cause a variety of problems. For example, in transportation equipment such as automobiles and trains, the vibrations themselves and the noise they generate may reduce the comfort of the occupants. In home appliances and audio equipment, the noise generated by vibrations may cause discomfort to the user. Furthermore, in precision instruments, for example, vibrations may interfere with the operation of the equipment.
[0003] To suppress the occurrence of these problems, various vibration damping technologies have been proposed. For example, in the field of buildings and structures, methods such as incorporating vibration damping members such as dampers, or adopting members with shapes that easily dampen vibrations in the components that make up buildings, etc., are frequently used. However, the method of incorporating vibration damping members may lead to an increase in the number of components in industrial products, etc. Furthermore, methods of damping vibrations by the shape of components are difficult to apply to transportation equipment, home appliances, precision instruments, etc., where the dimensions, mass, and shape of the components are greatly constrained.
[0004] To address these problems, methods are being considered for assembling industrial products and the like using components made from highly vibration-damping aluminum alloys, taking advantage of the characteristics of aluminum alloys, such as being relatively lightweight and having excellent workability. For example, Patent Document 1 describes a method for manufacturing an aluminum alloy vibration-damping material, in which an aluminum alloy ingot containing Fe: 0.5 to 20 wt%, with the remainder being Al and unavoidable impurities, is subjected to plastic deformation with a reduction ratio of 30% or more. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 3-223446 [Overview of the project] [Problems that the invention aims to solve]
[0006] In recent years, there has been a demand for aluminum alloy materials with even higher vibration damping capabilities than the aluminum alloy vibration damping material described in Patent Document 1.
[0007] This invention was made in view of the above background, and aims to provide an aluminum alloy material with high vibration damping properties, a component for precision equipment, and a method for manufacturing an aluminum alloy material. [Means for solving the problem]
[0008] One aspect of the present invention is, The chemical composition consists of Fe: 0.30% to 3.0% by mass, with the remainder being Al and unavoidable impurities. The system comprises an Al matrix and second-phase particles dispersed within the Al matrix, with 100 second-phase particles per mm having a maximum diameter of 7 μm or more and less than 10 μm. 2 The aluminum alloy material has the above-described metallic structure.
[0009] Other aspects of the present invention include: The above-mentioned aluminum alloy material is used for precision instrument parts.
[0010] Further aspects of the present invention include: The above-mentioned method for manufacturing aluminum alloy material, Cast an ingot having the aforementioned chemical components, The present invention relates to a method for manufacturing an aluminum alloy material, wherein the ingot is then subjected to hot extrusion while its temperature is 400°C or lower. [Effects of the Invention]
[0011] In the aforementioned aluminum alloy material, the number of second-phase particles with a maximum diameter of 7 μm or more and less than 10 μm is 100 particles / mm².2 It is as described above. Thereby, the vibration applied from the outside to the aluminum alloy material can be efficiently attenuated by the interaction between the second-phase particles and dislocations in the Al matrix. As a result, the vibration damping performance can be enhanced compared with conventional aluminum alloy materials.
[0012] Accordingly, according to the above aspect, it is possible to provide an aluminum alloy material having excellent vibration damping performance, a component for precision equipment, and a method for producing the aluminum alloy material. Brief Description of the Drawings
[0013] [Figure 1] It is a side view showing the main part of a loss coefficient measurement apparatus in an example. [Figure 2] It is an explanatory diagram showing an example of an amplitude-frequency curve in an example. Modes for Carrying Out the Invention
[0014] (Aluminum Alloy Material) [Chemical Components] The aluminum alloy material contains Al (aluminum) and one or two or more additive elements for forming second-phase particles in the Al matrix. As the additive elements, for example, Fe (iron), Mn (manganese), Si (silicon), Cu (copper), Mg (magnesium), Zn (zinc), Ni (nickel), Cr (chromium), Ti (titanium), V (vanadium), Zr (zirconium) and the like can be used. By adding these additive elements into the aluminum alloy material, second-phase particles containing the additive elements can be formed in the Al matrix.
[0015] ·Fe (iron): 0.30 mass% or more and 3.0 mass% or less The aluminum alloy material contains Fe in an amount of 0.30 mass% or more and 3.0 mass% or less. By setting the Fe content to 0.30 mass% or more, the amount of second-phase particles in the Al matrix can be increased, and the vibration damping property of the aluminum alloy material can be improved. From the viewpoint of further improving the vibration damping property of the aluminum alloy material, the Fe content is preferably 0.50 mass% or more, more preferably 0.70 mass% or more, still more preferably 1.0 mass% or more, and particularly preferably 1.2 mass% or more.
[0016] On the other hand, if the Fe content is excessively high, coarse second-phase particles tend to be formed in the aluminum alloy material, which may cause deterioration of extrudability and rollability. By setting the Fe content to 3.0 mass% or less, preferably 2.8 mass% or less, more preferably 2.5 mass% or less, still more preferably 2.0 mass% or less, and particularly preferably 1.8 mass% or less, the vibration damping property of the aluminum alloy material can be improved while easily avoiding such a problem.
[0017] In configuring the preferable range of the Fe content, the aforementioned upper limit and lower limit of the Fe content can be arbitrarily combined. For example, the preferable range of the Fe content may be 0.50 mass% or more and 2.8 mass% or less, 0.70 mass% or more and 2.5 mass% or less, 1.0 mass% or more and 2.0 mass% or less, or 1.2 mass% or more and 1.8 mass% or less.
[0018] ·Mn: 0.010 mass% or more and 1.50 mass% or less The aforementioned aluminum alloy material may contain 0.010% by mass or more and 1.50% by mass or less of Mn. By increasing the Mn content to 0.010% by mass or more, the amount of second-phase particles in the Al matrix can be increased, and the vibration damping properties of the aluminum alloy material can be further improved. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable to have 0.010% by mass or more, more preferably 0.050% by mass or more, even more preferably 0.10% by mass or more, and particularly preferably 0.30% by mass or more.
[0019] On the other hand, if the Mn content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in extrudeability and rollability. From the viewpoint of easily avoiding such problems while obtaining the effect of improving vibration damping, it is preferable to have a Mn content of 1.50 mass% or less, more preferably 1.00 mass% or less, even more preferably 0.80 mass% or less, and particularly preferably 0.50 mass% or less.
[0020] In determining a preferred range for the Mn content, the upper and lower limits for the Mn content described above can be arbitrarily combined. For example, the preferred range for the Mn content may be 0.010% by mass or more and 1.50% by mass or less, 0.050% by mass or more and 1.00% by mass or less, 0.10% by mass or more and 0.80% by mass or less, or 0.30% by mass or more and 0.50% by mass or less.
[0021] ·Si: 0.0050 mass% or more and 3.0 mass% or less The aluminum alloy material may contain 0.0050% by mass or more and 3.0% by mass or less of Si. By increasing the Si content to 0.0050% by mass or more, the amount of second-phase particles in the Al matrix can be increased, and the vibration damping properties of the aluminum alloy material can be further improved. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable to have a Si content of 0.0050% by mass or more, more preferably 0.010% by mass or more, even more preferably 0.040% by mass or more, and particularly preferably 0.10% by mass or more.
[0022] On the other hand, if the Si content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in extrudeability and rollability. In this case, the amount of additive elements dissolved in the Al matrix increases, which may lead to a decrease in vibration damping properties. From the viewpoint of avoiding these problems and obtaining the effect of improving vibration damping properties, it is preferable to have a Si content of 3.0 mass% or less, more preferably 2.6 mass% or less, even more preferably 2.2 mass% or less, and particularly preferably 2.0 mass% or less.
[0023] In determining the preferred range for the Si content, the upper and lower limits for the Si content described above can be arbitrarily combined. For example, the preferred range for the Si content may be 0.0050% by mass or more and 3.0% by mass or less, 0.010% by mass or more and 2.6% by mass or less, 0.040% by mass or more and 2.2% by mass or less, or 0.10% by mass or more and 2.0% by mass or less.
[0024] ·Ni: 0.010 mass% or more and 5.0 mass% or less The aluminum alloy material may contain 0.010% by mass or more and 5.0% by mass or less of Ni. By increasing the Ni content to 0.010% by mass or more, the amount of second-phase particles in the Al matrix can be increased, thereby improving the vibration damping properties of the aluminum alloy material. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable to have a Ni content of 0.010% by mass or more, more preferably 0.10% by mass or more, even more preferably 0.50% by mass or more, and particularly preferable to have a Ni content of 1.00% by mass or more.
[0025] On the other hand, if the Ni content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in extrudeability and rollability. It is preferable to have a Ni content of 5.0 mass% or less, more preferably 4.0 mass% or less, even more preferably 3.0 mass% or less, and particularly preferably 2.0 mass% or less. By setting the Ni content to the above values, it is possible to easily avoid these problems while improving the vibration damping properties of the aluminum alloy material.
[0026] In determining the preferred range for the Ni content, the upper and lower limits for the Ni content described above can be arbitrarily combined. For example, the preferred range for the Ni content may be 0.010% by mass or more and 5.0% by mass or less, 0.10% by mass or more and 4.0% by mass or less, 0.50% by mass or more and 3.0% by mass or less, or 1.00% by mass or more and 4.0% by mass or less.
[0027] ·Cu: 0.0030 mass% or more and 0.50 mass% or less The aluminum alloy material may contain Cu in an amount of 0.0030% by mass or more and 0.50% by mass or less. By increasing the Cu content to 0.0030% by mass or more, the amount of second-phase particles in the Al matrix can be increased, and the vibration damping properties of the aluminum alloy material can be further improved. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable that the Cu content be 0.0030% by mass or more, more preferably 0.0080% by mass or more, even more preferably 0.010% by mass or more, and particularly preferably 0.012% by mass or more.
[0028] On the other hand, if the Cu content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in extrudeability and rollability. In this case, the amount of additive elements dissolved in the Al matrix increases, which may lead to a decrease in vibration damping properties. From the viewpoint of easily avoiding these problems and obtaining the effect of improving vibration damping properties, it is preferable to have a Cu content of 0.50 mass% or less, more preferably 0.40 mass% or less, even more preferably 0.30 mass% or less, and particularly preferably 0.20 mass% or less.
[0029] In determining a preferred range for the Cu content, the upper and lower limits for the Cu content described above can be arbitrarily combined. For example, the preferred range for the Cu content may be 0.0030% by mass or more and 0.50% by mass or less, 0.0080% by mass or more and 0.40% by mass or less, 0.010% by mass or more and 0.30% by mass or less, or 0.012% by mass or more and 0.20% by mass or less.
[0030] ·Mg: 0.0050 mass% or more and 3.0 mass% or less The aluminum alloy material may contain 0.0050% by mass or more and 3.0% by mass or less of Mg. By increasing the Mg content to 0.0050% by mass or more, the amount of second-phase particles in the Al matrix can be increased, and the vibration damping properties of the aluminum alloy material can be further improved. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable that the Mg content be 0.0050% by mass or more, more preferably 0.010% by mass or more, even more preferably 0.020% by mass or more, and particularly preferably 0.050% by mass or more.
[0031] On the other hand, if the Mg content is excessively high, the amount of additive elements dissolved in the Al matrix increases, which may lead to a decrease in extrudeability and rollability. From the viewpoint of avoiding such problems and obtaining the effect of improving vibration damping, it is preferable to have a Mg content of 3.0 mass% or less, more preferably 2.0 mass% or less, even more preferably 1.5 mass% or less, and particularly preferably 1.0 mass% or less.
[0032] In determining a preferred range for the Mg content, the upper and lower limits for the Mg content described above can be arbitrarily combined. For example, the preferred range for the Mg content may be 0.0050% by mass or more and 3.0% by mass or less, 0.010% by mass or more and 2.0% by mass or less, 0.020% by mass or more and 1.5% by mass or less, or 0.050% by mass or more and 1.0% by mass or less.
[0033] ·Zn: 0.10 mass% or more and 0.50 mass% or less The aluminum alloy material may contain 0.10% by mass or more and 0.50% by mass or less of Zn. By increasing the Zn content to 0.10% by mass or more, the amount of second-phase particles in the Al matrix can be increased, and the vibration damping properties of the aluminum alloy material can be further improved. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable that the Zn content be 0.10% by mass or more, more preferably 0.15% by mass or more, even more preferably 0.18% by mass or more, and particularly preferably 0.20% by mass or more.
[0034] On the other hand, if the Zn content is excessively high, the amount of additive elements dissolved in the Al matrix increases, which may lead to a decrease in vibration damping performance. From the viewpoint of easily avoiding such problems and obtaining the effect of improving vibration damping performance, it is preferable to have a Zn content of 0.50 mass% or less, more preferably 0.45 mass% or less, even more preferably 0.42 mass% or less, and particularly preferably 0.40 mass% or less.
[0035] In determining the preferred range for the Zn content, the upper and lower limits for the Zn content described above can be arbitrarily combined. For example, the preferred range for the Zn content may be 0.10% by mass or more and 0.50% by mass or less, 0.15% by mass or more and 0.20% by mass or less, 0.18% by mass or more and 0.42% by mass or less, or 0.20% by mass or more and 0.40% by mass or less.
[0036] ·Cr: 0.050 mass% or more and 0.30 mass% or less The aforementioned aluminum alloy material may contain Cr in an amount of 0.050% by mass or more and 0.30% by mass. By increasing the Cr content to 0.050% by mass or more, the vibration damping properties of the aluminum alloy material can be further improved. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable that the Cr content be 0.050% by mass or more, more preferably 0.070% by mass or more, even more preferably 0.090% by mass or more, and particularly preferable 0.10% by mass or more.
[0037] On the other hand, if the Cr content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in extrudeability and rollability. From the viewpoint of obtaining the effect of improving vibration damping while avoiding such problems, it is preferable to have a Cr additive content of 0.30 mass% or less, more preferably 0.26 mass% or less, even more preferably 0.22 mass% or less, and particularly preferably 0.20 mass% or less.
[0038] In determining the preferred range for the content of Cr additives, the upper and lower limits for the content of Cr additives mentioned above can be arbitrarily combined. For example, the preferred range for the content of Cr additives may be 0.050% by mass or more and 0.30% by mass or less, 0.070% by mass or more and 0.26% by mass or less, 0.090% by mass or more and 0.22% by mass or less, or 0.10% by mass or more and 0.20% by mass or less.
[0039] ·Ti: 0.010 mass% or more and 0.30 mass% or less The aluminum alloy material may contain 0.010% by mass or more and 0.30% by mass or less of Ti. By increasing the Ti content to 0.010% by mass or more, the amount of second-phase particles in the Al matrix can be increased, thereby improving the vibration damping properties of the aluminum alloy material. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable that the Ti content be 0.010% by mass or more, more preferably 0.050% by mass or more, even more preferably 0.080% by mass or more, and particularly preferably 0.10% by mass or more.
[0040] On the other hand, if the Ti content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in extrudeability and rollability. It is preferable to have a Ti content of 0.30 mass% or less, more preferably 0.26 mass% or less, even more preferably 0.22 mass% or less, and particularly preferably 0.20 mass% or less. By setting the Ti content to the above values, it is possible to easily avoid these problems while improving the vibration damping properties of the aluminum alloy material.
[0041] In determining the preferred range for the Ti content, the upper and lower limits for the Ti content mentioned above can be arbitrarily combined. For example, the preferred range for the Ti content may be 0.010% by mass or more and 0.30% by mass or less, 0.050% by mass or more and 0.26% by mass or less, 0.080% by mass or more and 0.22% by mass or less, or 0.10% by mass or more and 0.20% by mass or less.
[0042] ·V: 0.010 mass% or more and 0.30 mass% or less The aluminum alloy material may contain 0.010% by mass or more and 0.30% by mass or less of V. By increasing the V content to 0.010% by mass or more, the amount of second-phase particles in the Al matrix can be increased, thereby improving the vibration damping properties of the aluminum alloy material. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable that the V content be 0.010% by mass or more, more preferably 0.020% by mass or more, even more preferably 0.080% by mass or more, and particularly preferably 0.10% by mass or more.
[0043] On the other hand, if the V content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in extrudeability and rollability. It is preferable to have a V content of 0.30 mass% or less, more preferably 0.28 mass% or less, even more preferably 0.25 mass% or less, and particularly preferably 0.20 mass% or less. By setting the V content to the above values, it is possible to improve the vibration damping properties of the aluminum alloy material while easily avoiding the above problems.
[0044] In determining the preferred range for the V content, the upper and lower limits for the V content described above can be arbitrarily combined. For example, the preferred range for the V content may be 0.010% by mass or more and 0.30% by mass or less, 0.020% by mass or more and 0.28% by mass or less, 0.080% by mass or more and 0.25% by mass or less, or 0.10% by mass or more and 0.20% by mass or less.
[0045] ·Zr: 0.0010 mass% or more and 0.30 mass% or less The aluminum alloy material may contain 0.0010% by mass or more and 0.30% by mass or less of Zr. By increasing the Zr content to 0.0010% by mass or more, the vibration damping properties of the aluminum alloy material can be further improved. From the viewpoint of further improving the vibration damping properties of the aluminum alloy material, it is preferable that the Zr content be 0.0010% by mass or more, more preferably 0.0040% by mass or more, even more preferably 0.0080% by mass or more, and particularly preferable 0.010% by mass or more.
[0046] On the other hand, if the Zr content is excessively high, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in rollability. From the viewpoint of obtaining the effect of improving vibration damping while avoiding such problems, it is preferable to have a Zr content of 0.30 mass% or less, more preferably 0.026 mass% or less, even more preferably 0.22 mass% or less, and particularly preferably 0.20 mass% or less.
[0047] In determining the preferred range for the Zr content, the upper and lower limits for the Zr content described above can be arbitrarily combined. For example, the preferred range for the Zr content may be 0.0010% by mass or more and 0.30% by mass or less, 0.0040% by mass or more and 0.026% by mass or less, 0.0080% by mass or more and 0.22% by mass or less, or 0.010% by mass or more and 0.20% by mass or less.
[0048] [Metal structure] The aluminum alloy material has second-phase particles dispersed in an Al matrix. The second-phase particles are composed of, for example, Al-Fe compounds, Si, Al-Fe-Mn compounds, Al-Fe-Si compounds, Al-Mn compounds, Al-Mn-Si compounds, Al-Fe-Mn-Si compounds, Al-Cu compounds, Al-Mg compounds, Mg-Si compounds, Al-Mg-Zn compounds, Al-Cu-Zn compounds, Al-Ni compounds, Al-Cr compounds, Al-Ti compounds, Al-V compounds, Al-Zr compounds, etc. The second-phase particles may be precipitates or crystals.
[0049] • Number of second-phase particles per unit area with a maximum diameter of 7 μm to 10 μm In the aforementioned aluminum material, the number of second-phase particles with a maximum diameter of 7 μm to 10 μm per unit area is 100 particles / mm². 2 That concludes the report. The number of second-phase particles with a maximum diameter of 7 μm to 10 μm per unit area is 400 particles / mm². 2 It is more preferable that the value be greater than or equal to 800 pieces / mm 2 It is even more preferable that the number be greater than or equal to 1000 pieces / mm 2 It is especially preferable that the above conditions are met.
[0050] By increasing the number of second-phase particles with a maximum diameter of 7 μm or more and 10 μm or less per unit area, the interaction between the second-phase particles and dislocations can be further strengthened. As a result, the vibration damping property of the aluminum alloy material can be further improved. The number of second-phase particles with a maximum diameter of 7 μm or more and 10 μm or less per unit area has no particular upper limit from the viewpoint of improving vibration damping property, but may be, for example, 10000 particles / mm 2 or less, 8000 particles / mm 2 or less, 6000 particles / mm 2 or less, or 4000 particles / mm 2 or less.
[0051] The aforementioned number of second-phase particles with a maximum diameter of 7 μm or more and 10 μm or less per unit area can be calculated as follows. First, after polishing the cross-section of the material, a composition image of the surface is acquired using an electron probe microanalyzer. The field of view area of the composition image only needs to be large enough to represent the metal structure. Specifically, for example, by setting the field of view area to 0.01 mm 2 or more, a composition image representing the metal structure of the entire material can be acquired.
[0052] The obtained composition image is analyzed using an image analyzer, and the contour lines of the second-phase particles present in the field of view are extracted. Then, for each individual second-phase particle, two points with the largest mutual distance among the points on the contour line are determined. The distance between these two points is defined as the maximum diameter of each second-phase particle. After determining the maximum diameters of the second-phase particles present in the field of view in this manner, the number of second-phase particles having a maximum diameter of 7 μm or more and 10 μm or less is counted, and by converting this number to the number per 1 mm 2 (number per unit area), the aforementioned number of second-phase particles with a maximum diameter of 7 μm or more and 10 μm or less per unit area can be obtained.
[0053] The cross-section of the object to be observed is not particularly limited. For example, if the aluminum alloy material is a rolled plate, the cross-section of the object to be observed may be an LT-ST plane (i.e., a cross-section perpendicular to the rolling direction), an L-LT plane (i.e., a cross-section parallel to the plate surface), or an L-ST plane (i.e., a cross-section parallel to the rolling direction). Furthermore, if the aluminum alloy material is an extruded material, the cross-section of the object to be observed may be a cross-section parallel to the extrusion direction, or a cross-section perpendicular to the extrusion direction. Moreover, the cross-section of the object to be observed may be any other cross-section.
[0054] ·Crystal grain size In the aforementioned aluminum alloy material, it is preferable that the proportion of crystals with a grain size of 3 μm or more that have a grain size of 3 μm or more and 10 μm or less is 50% or more, and that the average grain size of the crystals with a grain size of 3 μm or more is 50 μm or less.
[0055] When, among crystals with a grain size of 3 μm or more, the proportion of crystals with a grain size of 3 μm to 10 μm is 50% or more, and the average grain size of the crystals with a grain size of 3 μm is 50 μm or less, there will be many grain boundaries, and the interaction between dislocations present near the grain boundaries and second-phase particles can further improve the vibration damping properties of the aluminum alloy material. More preferably, among crystals with a grain size of 3 μm or more, the proportion of crystals with a grain size of 3 μm to 10 μm is 60% or more, and the average grain size of the crystals with a grain size of 3 μm or more is 30 μm or less.
[0056] In measuring crystal grain size, the cross-section of the object to be observed is not particularly limited. First, the cross-section of the material for microstructure observation was processed using a known method such as polishing to prepare a sample for measurement. It is preferable to remove the polished layer by etching or other means. Next, the orientation information of the texture was obtained by measuring this polished surface with a backscatter electron diffraction analyzer (SEM-EBSD) attached to a scanning electron microscope. The measurement area of the sample was set to 200 μm × 200 μm or larger, and the measurement step interval was set to 1.0 μm, but if sufficient data cannot be obtained under these conditions, it was set to 0.5 μm.
[0057] Next, the grain size was calculated from the obtained orientation data using EBSD analysis software (TSL's "OIM Analysis"). In this process, crystal boundaries with a misorientation of 5° or more were considered grain boundaries, and the diameter calculated as a circle equivalent was defined as the grain size.
[0058] (Manufacturing method for aluminum alloy materials) The aluminum alloy material can be produced, for example, by casting an ingot having the specific chemical components, and then appropriately combining drawing processes such as extrusion, drawing, and rolling, as well as heat treatment, on the ingot depending on the casting method.
[0059] For example, one manufacturing method can involve casting a billet as an ingot using a DC casting method or the like, and then sequentially performing processes such as extrusion and drawing on the billet as part of a stretching process.
[0060] By extruding the billet, the number of second-phase particles with a maximum diameter of 7 μm or more and less than 10 μm can be easily reduced to 100 particles / mm². 2This is preferable as it allows for the above conditions to be met. Furthermore, by extruding the billet, it is preferable that the proportion of crystals with a grain size of 3 μm or more that are between 3 μm and 10 μm is 50% or more, and the average grain size of the crystals with a grain size of 3 μm or more is 50 μm or less. However, a method in which a slab as an ingot is cast by DC casting or the like, and then the slab is sequentially rolled, may also be employed.
[0061] The following describes examples of extrusion and drawing processes performed on billets manufactured by DC casting. However, the extrusion and drawing processes described below are not limited to those described below.
[0062] In DC casting, the casting speed is preferably within the range of 20 mm / min to 100 mm / min. By keeping the casting speed within this specific range, the formation of coarse second-phase particles can be suppressed.
[0063] In this embodiment, after DC casting, the billet may be heated and homogenized before extrusion, or extrusion may be performed without homogenization. When homogenization is performed, the heating temperature can be appropriately set from, for example, a range of 200°C to 620°C. The heating temperature in the homogenization is preferably 500°C or lower, and more preferably 340°C or lower. In this case, the second phase particles in the Al matrix can be made finer and the perimeter length of the second phase particles can be made larger. As a result, vibration damping can be further improved through the interaction between dislocations and second phase particles.
[0064] Furthermore, in the homogenization process, heating may be terminated immediately after the billet reaches the heating temperature, or the heating temperature may be maintained for a certain period of time. In the latter case, the maintenance time can be 50 hours or less.
[0065] If the heating temperature during the homogenization process is below 200°C, the homogenization of the billet may be insufficient. Furthermore, if the heating temperature during the homogenization process exceeds 620°C or the holding time exceeds 50 hours, coarse second-phase particles are more likely to form in the billet, which may lead to a decrease in vibration damping performance.
[0066] Next, the billet is extruded to produce the extruded material. Preferably, the billet temperature at the start of extrusion is between 250°C and 400°C. If the billet temperature at the start of rolling is below 250°C, the billet is difficult to deform, making extrusion difficult. If the billet temperature at the start of extrusion exceeds 400°C, the crystal grains become coarse, which may lead to a decrease in vibration damping properties. More preferably, the billet temperature at the start of extrusion is between 250°C and 350°C.
[0067] The extrusion ratio (cross-sectional area before extrusion / cross-sectional area after extrusion) in the extrusion process is preferably between 2 and 200. An extrusion ratio of less than 2 in the extrusion process is undesirable because a significant improvement in vibration damping cannot be expected. An extrusion ratio exceeding 200 in the extrusion process is undesirable because there is a risk of the material breaking during processing. A more preferable extrusion ratio in the extrusion process is between 3 and 100.
[0068] When heating the billet before extrusion, heating may be stopped immediately after the billet reaches the desired temperature, or the desired temperature may be maintained for a certain period of time. In the latter case, the holding time can be 30 hours or less. If the holding time exceeds 30 hours, coarse second-phase particles are more likely to form in the billet, which may lead to a decrease in vibration damping properties.
[0069] In this embodiment, the extruded material obtained by extrusion may be used as the aluminum alloy material. Alternatively, the aluminum alloy material obtained by extrusion may be heated and annealed. The heating temperature in this annealing can be appropriately set from the range of 200°C to 400°C. If the heating temperature in annealing is less than 200°C, the annealing effect may be insufficient. If the heating temperature in annealing exceeds 400°C, coarse second-phase particles are more likely to form in the extruded material, which may lead to a decrease in vibration damping performance.
[0070] In the annealing process, heating may be terminated immediately after reaching the heating temperature, or the heating temperature may be maintained for a certain period of time. In the latter case, the holding time can be 10 hours or less. If the holding time exceeds 10 hours, coarse second-phase particles are more likely to form in the extruded material, which may lead to a decrease in vibration damping properties.
[0071] In this embodiment, the aluminum alloy material obtained by extrusion can also be further subjected to drawing. In drawing, it is preferable to perform the drawing process so that the reduction ratio is 20% or more. This increases the dislocation density of the aluminum alloy material and further improves the vibration damping properties of the aluminum alloy material. The reduction ratio in drawing is preferably 20% or more, more preferably 40% or more, even more preferably 70% or more, and particularly preferably 80% or more.
[0072] The temperature during the drawing process is preferably 150°C or lower. If the temperature during the drawing process exceeds 150°C, a significant improvement in vibration damping cannot be expected, which is undesirable.
[0073] If the drawing process involves two or more passes, the extruded material can be heated between passes for intermediate annealing. The heating temperature for intermediate annealing can be set appropriately within the range of 200°C to 400°C. If the heating temperature for intermediate annealing is below 200°C, the effect of intermediate annealing may be insufficient. If the heating temperature for intermediate annealing exceeds 400°C, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in vibration damping performance.
[0074] Furthermore, during intermediate annealing, heating may be terminated immediately after reaching the heating temperature, or the heating temperature may be maintained for a certain period of time. In the latter case, the holding time can be 10 hours or less. If the holding time exceeds 10 hours, coarse second-phase particles are more likely to form in the aluminum alloy material, which may lead to a decrease in vibration damping properties.
[0075] When performing the intermediate annealing described above, it is preferable to perform the drawing so that the reduction in surface area after intermediate annealing is 50% or more. In other words, it is preferable that the difference between the cross-sectional area of the extruded material before resuming the drawing process after intermediate annealing and the cross-sectional area of the desired aluminum alloy material is 50% or more of the cross-sectional area of the extruded material before resuming the drawing process. This increases the dislocation density of the aluminum alloy material and improves the vibration damping properties of the aluminum alloy material.
[0076] In this embodiment, the aluminum alloy material after drawing may be heated to perform final annealing. The heating temperature in the final annealing can be appropriately set from the range of 100°C to 200°C. If the heating temperature in the final annealing is less than 100°C, the effect of the final annealing may be insufficient. If the heating temperature in the final annealing exceeds 200°C, the dislocation density may decrease significantly due to dislocation rearrangement or disappearance, which may lead to a decrease in vibration damping performance.
[0077] Furthermore, in the final annealing stage, heating may be terminated immediately after reaching the heating temperature, or the heating temperature may be maintained for a certain period of time. In the latter case, the holding time can be 10 hours or less. If the holding time exceeds 10 hours, the dislocation density may decrease due to dislocation rearrangement or disappearance, which may lead to a decrease in vibration damping performance.
[0078] Another method for manufacturing the aluminum alloy material is to cast strips as ingots using a continuous casting method such as a twin-roll continuous casting rolling method or a twin-belt continuous casting method, and then perform rolling as a stretching process on the strips.
[0079] In continuous casting, the casting speed is preferably within the range of 500 mm / min to 3000 mm / min. By keeping the casting speed within this specific range, the formation of coarse second-phase particles can be suppressed.
[0080] The aluminum alloy material can be obtained by performing continuous casting followed by one or more passes of rolling on the strip. In the rolling process, it is preferable to perform the rolling so that the total reduction ratio is 50% or more, similar to the processing conditions for DC casting described above. In other words, it is preferable that the difference between the thickness of the strip before rolling after continuous casting and the thickness of the desired aluminum alloy material is 50% or more of the thickness of the strip. This increases the dislocation density of the aluminum alloy material and further improves its vibration damping properties.
[0081] Furthermore, in this embodiment, as in the DC casting described above, intermediate annealing may be performed between rolling passes, or final annealing may be performed after the drawing process is completed. The processing conditions for intermediate annealing and final annealing in this embodiment, and their effects, are the same as the processing conditions for DC casting described above.
[0082] The aluminum alloy material manufactured as described above has excellent vibration damping properties and can therefore be suitably applied to precision equipment components that make up precision instruments. Examples of precision equipment components include those that make up cameras, audio equipment, office automation equipment, measuring devices, and the like. This makes it possible to suppress interference with the operation of precision instruments caused by vibration. [Examples]
[0083] Examples of the aluminum alloy material described above will be explained with reference to Figures 1 and 2. It should be noted that the specific embodiments of the aluminum alloy material according to the present invention are not limited to those shown in the following examples, and the configuration can be appropriately modified from the examples without impairing the spirit of the present invention.
[0084] The aluminum alloy material in this example can be manufactured by the following method. First, a billet having the chemical composition shown in Table 1 is cast by the DC casting method. This ingot is heated, and while the temperature of the ingot is at the temperature shown in the "Extrusion Start Temperature" column of Table 2, an extrusion process is carried out to produce an extruded material with the diameter shown in Table 2.
[0085] For test material 4-6, the drawing process is carried out so that the reduction ratio during the drawing process is the value shown in Table 2.
[0086] Test specimens 8-9 will undergo solution treatment under the conditions shown in Table 2. Furthermore, test specimen 9 will undergo heat treatment under the conditions shown in Table 2 after the solution treatment.
[0087] The number of second-phase particles with a maximum diameter of 7 μm or more and less than 10 μm in these test materials (per mm²) 2 The proportion of crystals with a grain size of 3 μm or more that have a grain size between 3 μm and 10 μm, the average grain size of crystals with a grain size of 3 μm or more, the method for calculating the loss factor η, and the method for evaluating the morphology of the crystal grains are as follows.
[0088] • Number of second-phase particles per unit area with a maximum diameter of 7 μm or more and less than 10 μm. First, a cross-section of the test material perpendicular to the extrusion or drawing direction is polished. An electron beam microanalyzer is used to observe a randomly selected observation point on the polished surface, and a backscattered electron image at a magnification of 1000x is obtained. In the backscattered electron image, the Al matrix and the second-phase particles dispersed in the Al matrix are displayed with different brightness levels.
[0089] Next, the backscattered electron image is binarized using an image processing device or the like to create a binarized image. The threshold value in the binarization process should be set appropriately so that the contours of the second-phase particles in the backscattered electron image are maintained even after the binarization process.
[0090] After extracting second-phase particles with a maximum diameter of 7 μm or more and less than 10 μm from this binarized image, the number of second-phase particles per unit area can be calculated by dividing the number of particles by the field of view area.
[0091] • The proportion of crystals with a grain size of 3 μm or more that have a grain size between 3 μm and 10 μm, and the average grain size of crystals with a grain size of 3 μm or more. The cross-section of the test material parallel to the extrusion or drawing direction was polished. Next, the polished surface was eroded to remove the polished layer. Then, the orientation information of the texture was obtained by measuring this polished surface with a backscatter electron diffraction analyzer (SEM-EBSD) attached to a scanning electron microscope. The measurement area of the sample was set to 200 μm × 200 μm or larger, and the measurement step interval was set to 1.0 μm, but if sufficient data could not be obtained under these conditions, it was set to 0.5 μm. Next, the grain size was calculated from the obtained orientation data using EBSD analysis software ("OIM Analysis" from TSL). In this case, crystal boundaries with a misorientation of 5° or more were considered as grain boundaries, and the diameter calculated as a circle equivalent was taken as the grain size.
[0092] Among crystals with a grain size of 3 μm or more, the proportion of crystals with a grain size between 3 μm and 10 μm was calculated by dividing the number of crystals with a grain size between 3 μm and 10 μm by the total number of crystals with a grain size of 3 μm or more, and multiplying by 100.
[0093] For crystals with a grain size of 3 μm or larger, the average grain size was calculated using the average number of crystals with a grain size of 3 μm or larger.
[0094] A free-resonance internal friction measuring device (JE-RT, manufactured by Nippon Techno Plus Co., Ltd.) can be used to measure the loss coefficient η. As shown in Figure 1, the measuring device 2 has a drive electrode 21 and an amplitude sensor 22 facing the drive electrode 21. A strip test piece S is placed horizontally between the drive electrode 21 and the amplitude sensor 22, and the strip test piece S is fixed with a thin wire 23 at the position that will be a node of vibration. In this state, by passing an alternating current through the drive electrode 21 and applying a Coulomb force to the strip test piece S, the strip test piece S can be vibrated. Then, by measuring the amplitude of the strip test piece S using the amplitude sensor 22, the vibration waveform can be obtained.
[0095] In this example, an electrostatic force is generated from the driving electrode 21 to forcibly vibrate the strip-shaped test piece S, and its amplitude is measured. By vibrating the strip-shaped test piece S while sweeping the vibration frequency, an amplitude-frequency curve like the one shown in Figure 2 can be obtained. In Figure 2, the vertical axis is the common logarithm of the amplitude, and the horizontal axis is the frequency (Hz).
[0096] The loss coefficient η of the test material can be calculated using the full width at half maximum (FWHM) method based on the amplitude-frequency curve shown in Figure 2. First, the frequency at which the amplitude is maximum on the amplitude-frequency curve is determined, and this frequency is defined as the resonant frequency f0. Next, the FWHM Δf of the resonant peak is determined. Specifically, the FWHM Δf can be calculated as follows: First, in the range of frequencies lower than the resonant frequency f0, the frequency f1 at which the amplitude is half of the amplitude A0 at the resonant frequency f0 is determined. Next, in the range of frequencies higher than the resonant frequency f0, the frequency f2 at which the amplitude is half of the amplitude A0 at the resonant frequency f0 is determined. The difference between the frequency f2 and the frequency f1 obtained in this way, f2-f1, is the FWHM Δf.
[0097] By substituting the resonant frequency f0 and half-width Δf obtained above into the following equation (1), the loss coefficient η can be calculated.
[0098]
number
[0099] [Table 1]
[0100] [Table 2]
[0101] As shown in Table 2, the number of second-phase particles with a longest diameter of 7 μm or more and less than 10 μm per unit area in test materials 1 to 7 is within the specified range. Therefore, the loss coefficient value for these test materials is 5.0 × 10⁻⁶. -4 That concludes the explanation. Therefore, these test materials possess excellent vibration damping properties.
[0102] Test materials 4-7 are manufactured by performing a drawing process after an extrusion process on an ingot produced by a casting process. This makes it possible to further increase the dislocation density of the aluminum alloy material, so test materials 4-7 have even better vibration damping properties than test materials 1-3, which have not undergone the drawing process.
[0103] The number of second-phase particles with a maximum diameter of 7 μm or more and less than 10 μm per unit area in test material 8 and test material 9 is smaller than the specified range. Therefore, the vibration damping properties of these test materials are inferior to those of test materials 1 to 7.
[0104] Although embodiments of the aluminum alloy material, precision instrument parts, and method for manufacturing the aluminum alloy material have been described above based on the examples, the specific embodiments of the aluminum alloy material, precision instrument parts, and method for manufacturing the aluminum alloy material according to the present invention are not limited to the embodiments described in the examples, and the configuration can be appropriately changed without impairing the spirit of the present invention.
[0105] For example, the aluminum alloy material may take the following forms [1] to [3].
[0106] [1] Fe: Contains 0.30% to 3.0% by mass, with the remainder being Al and unavoidable impurities, The system comprises an Al matrix and second-phase particles dispersed within the Al matrix, with 100 second-phase particles per mm having a maximum diameter of 7 μm or more and less than 10 μm. 2 An aluminum alloy material having the above-mentioned metallic structure.
[0107] [2] The aluminum alloy material according to [1], further containing one or more elements selected from the group consisting of Mn: 0.10 mass% to 1.50 mass%, Si: 0.0050 mass% to 3.0 mass%, Cu: 0.0030 mass% to 0.50 mass%, Mg: 0.0050 mass% to 3.0 mass%, Zn: 0.10 mass% to 0.50 mass%, Ni: 0.10 mass% to 5.0 mass%, Cr: 0.050 mass% to 0.30 mass%, Ti: 0.050 mass% to 0.30 mass%, V: 0.050 mass% to 0.30 mass%, and Zr: 0.0010 mass% to 0.30 mass%.
[0108] [3] The aluminum alloy material according to [1] or [2], wherein, in the metal structure, the proportion of crystals with a grain size of 3 μm or more that have a grain size of 3 μm or more is 50% or more, and the average grain size of the crystals with a grain size of 3 μm or more is 50 μm or less.
[0109] Furthermore, the precision instrument component may take the form described in [4] below. Precision instrument parts made of aluminum alloy material as described in any one of [4][1] to [3].
[0110] Furthermore, the method for manufacturing the aluminum alloy material may take the forms described in [5] to [6] below. A method for manufacturing an aluminum alloy material as described in any one of [5][1] to [3], Cast an ingot having the aforementioned chemical components, A method for manufacturing an aluminum alloy material, comprising then hot extruding the ingot while its temperature is 400°C or lower.
[0111] [6] A method for manufacturing an aluminum alloy material according to [5], wherein the aluminum alloy material obtained by hot extrusion is subjected to drawing. [Explanation of symbols]
[0112] 21 Driving electrode 22 Amplitude Sensor 23 Thin line
Claims
1. Fe: Contains 0.30% to 3.0% by mass, with the remainder being Al and unavoidable impurities, The system comprises an Al matrix and second-phase particles dispersed within the Al matrix, with 100 second-phase particles per mm having a maximum diameter of 7 μm or more and less than 10 μm. 2 An aluminum alloy material having the above-mentioned metallic structure.
2. The aluminum alloy material according to claim 1, further containing one or more elements selected from the group consisting of Mn: 0.010 mass% to 1.50 mass%, Si: 0.0050 mass% to 3.0 mass%, Cu: 0.0030 mass% to 0.50 mass%, Mg: 0.0050 mass% to 3.0 mass%, Zn: 0.10 mass% to 0.50 mass%, Ni: 0.010 mass% to 5.0 mass%, Cr: 0.050 mass% to 0.30 mass%, Ti: 0.010 mass% to 0.30 mass%, V: 0.010 mass% to 0.30 mass%, and Zr: 0.0010 mass% to 0.30 mass%.
3. The aluminum alloy material according to claim 1, wherein, in the metal structure, the proportion of crystals with a grain size of 3 μm or more that have a grain size of 3 μm or more is 50% or more, and the average grain size of the crystals with a grain size of 3 μm or more is 50 μm or less.
4. A precision instrument component made of an aluminum alloy material according to any one of claims 1 to 3.
5. A method for manufacturing an aluminum alloy material according to any one of claims 1 to 3, Cast an ingot having the aforementioned chemical components, A method for manufacturing an aluminum alloy material, comprising then hot extruding the ingot while its temperature is 400°C or lower.
6. The method for manufacturing an aluminum alloy material according to claim 5, wherein the aluminum alloy material obtained by the hot extrusion is subjected to drawing.
Citation Information
Patent Citations
Manufacture of aluminum alloy high damping material
JP1991223446A